2020
DOI: 10.1061/(asce)mt.1943-5533.0003459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixture Design Parameters on the Mechanical Behavior of High-Performance Fiber-Reinforced Concretes

Abstract: Bu çalışmada ISO/ITU H264/AVC video kodlaması kullanılarak kodlanmış bir video dizisinde makro-öbek bileşenleri çeşitleri analiz edilerek ani ve dereceli sahne kesikleri kestirimi uygulamaları için metodlar önerilmiştir. Sıkıştırılmış sahada yapılan analiz, video dizisinin tamamen sıkıştırmayı çözme sürecine gerek duyulmadan sahne geçişlerininin sezimini gerçeklestirmistir. Önerilen algoritmayi gerçeklemek için çesitli test video dizileri ISO/ITU H264/AVC kodlanarak QCIF çözünürlüğüne indirgenip, kodlanmistir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These improvements in the interfacial frictional bonding were attributed to the hydration acceleration and seeding effect coupled with the large surface areas of nanomaterials. 59,60 In a recent work of the author, 61 it was shown by SEM images that fibers pulled out of mixtures without nanomaterials were not densely covered by the remainders of cementitious matrix and pull-out process was easier. However, for fibers pulled out of mixtures with nanomaterials, pull-out process was harder, the fibers were covered with the remainders of the cementitious matrix and the surface of the fibers were rough and/or fibrillated, all of which suggesting for a better fiber-matrix frictional bonding.…”
Section: Load Versus Mid-span Deflection Curvesmentioning
confidence: 99%
“…These improvements in the interfacial frictional bonding were attributed to the hydration acceleration and seeding effect coupled with the large surface areas of nanomaterials. 59,60 In a recent work of the author, 61 it was shown by SEM images that fibers pulled out of mixtures without nanomaterials were not densely covered by the remainders of cementitious matrix and pull-out process was easier. However, for fibers pulled out of mixtures with nanomaterials, pull-out process was harder, the fibers were covered with the remainders of the cementitious matrix and the surface of the fibers were rough and/or fibrillated, all of which suggesting for a better fiber-matrix frictional bonding.…”
Section: Load Versus Mid-span Deflection Curvesmentioning
confidence: 99%
“…e experimental tests investigated at the material level demonstrated that steel fibers improved the resistance to crack growth, reduced deflection, and increased the fatigue life and impact resistance of plain concrete under different loads. e inclusion of steel fibers in concrete can greatly enhance static flexural strength, impact strength, shear and torsional strength, direct tensile strength, fatigue strength, impact resistance, ductility, and failure toughness [7][8][9]. e most substantial advantage of adding fibers to concrete is the improvement in impact resistance [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%